A review of hybrid energy technologies tenets, controls and combinational strategies - Naz, M.Y. (Elsevier Ltd, 2021)
The biggest problem that has been faced globally is the extinction of natural resources for production of energy. Industries as well as consumers should devise some ways to generate energy by utilizing limited resources and hence making the system cost effective. The resources of renewable energy and their reserves are sources of survival in modern era. The ever-rising demand of electricity and the trend that has been shifted to electric vehicles require some devices that can be used for energy production, distribution and storage. The focus of this review is to deduce some efficient techniques utilizing the renewable energy resources that can be cost effective, environment friendly and most economical energy producers. This review also discusses the development of hybridized topologies and tenets, control and energy administrative policies, power electronics interface architectures, different methodologies applied in different hybrid energy systems, designing, types and application arenas. The objective was to uncover the evolution of hybrid energy systems by presenting the research that has already been conducted in this domain and to discuss diverse technologies and control mechanisms they have used in their research. Â© 2021 The Authors